2008
DOI: 10.3138/cjccj.50.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Predictors of Adult Criminality: A Meta-Analysis Drawn from the Prospective Longitudinal Literature

Abstract: du comportement criminel pour évaluer les répercussions des expériences vécues pendant la petite enfance et l'adolescence sur les comportements à l'âge adulte. Dans la présente méta-analyse, trente-huit études prospectives et longitudinales répondaient aux critères de sélection. Elles portaient sur divers facteurs liés à la petite enfance et à la famille permettant peut-être de prédire la participation éventuelle à un délit ou un crime à l'âge adulte. Les principaux résultats révèlent que des prédicateurs dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 49 publications
4
63
2
4
Order By: Relevance
“…These estimates are given in Table 21. It is not possible to combine the log-linear parameter estimates with the effect sizes presented by Leschied et al;193 however, the associations found were consistent with those from Leschied et al, 193 showing a strong relationship between mid-childhood externalising concerns and arrests (aged 17-19 years), and no evidence of a relationship between internalising concerns and arrests (aged 17-19 years). In extrapolations from short-term to long-term outcomes, we used the estimates from Leschied et al, 193 as these represented a meta-analysis of the majority of the studies which reported these associations and included studies with longer follow-up than that of Capaldi and Stoolmiller 194 (reported arrests aged 17-19 years).…”
Section: Criminalitysupporting
confidence: 56%
See 4 more Smart Citations
“…These estimates are given in Table 21. It is not possible to combine the log-linear parameter estimates with the effect sizes presented by Leschied et al;193 however, the associations found were consistent with those from Leschied et al, 193 showing a strong relationship between mid-childhood externalising concerns and arrests (aged 17-19 years), and no evidence of a relationship between internalising concerns and arrests (aged 17-19 years). In extrapolations from short-term to long-term outcomes, we used the estimates from Leschied et al, 193 as these represented a meta-analysis of the majority of the studies which reported these associations and included studies with longer follow-up than that of Capaldi and Stoolmiller 194 (reported arrests aged 17-19 years).…”
Section: Criminalitysupporting
confidence: 56%
“…The results are already included in the meta-analysis conducted by Leschied et al 193 Although it is unclear what inputs have been used in the meta-analysis, these are described as internalising concerns. This study is included in our analyses through inclusion of the meta-analysis by Leschied et al 193 Barkley et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations